Strategi Merancang Materi Nahwu Kreatif dan Menarik Berbasis Konten Instagram - Maulidiyah, Lailil; Sulaikho, Siti; Ni'am, Falahun; Ruwaida (Cordova Journal language and culture studies, 2024)
Designing creative and interesting nahwu material based on Instagram content can add methods or strategies to the learning process so that students feel not bored following the learning process. With an interesting learning method, students more easily understand the material delivered by educators. The Research and Development (R&D) method with a 4D model is used. The 4D model consists of 4 stages: define, design, develop, and disseminate. The results showed that at the define stage, students really need varied nahwu learning, such as in the form of content on social media that looks more interesting. At the design stage, researchers begin to design nahwu material so that students can use it as a learning reference. The next research will carry out the next two stages, namely development and disseminate.